The Effect of Democracy on Income: An Analysis of Countries Affected by Coups d’État - Saray, Ozan Mehmet (Panoeconomicus, 2018)
Although there is a considerable amount of study which examines the effect of democracy on national income, a limited number of papers analyses the effect of democracy on per capita income. The main objective of this research is to show the effect of democracy level on per capita income among new sample, 21 countries which share a similar coup d’état experience in their political history, to fulfil the gap in the literature. The countries selected are from different continents and are those most affected by coups. The impact of two different democracy indicators (Freedom House and Polity IV) on the per capita income of the countries in the period 2000-2014 is analysed. The results of the panel data estimation show that, an increase in democracy level has a positive effect on per capita income for both democracy indicators. As expected, the effect of the investment, secularism and education variables on income is positive, whereas the effect of population growth rate is negative. And trade has no definite effect on per capita income. Key words: Coup d’états, Democracy, Income, Panel data. JEL: P16, 010, I25, F10, C33.